2017
DOI: 10.1108/rpj-12-2015-0189
|View full text |Cite
|
Sign up to set email alerts
|

Deposition-induced effects of isotactic polypropylene and polycarbonate composites during fused deposition modeling

Abstract: Purpose Although the feasibility and effectiveness of the fused deposition modeling (FDM) method have been proposed and developed, studies of applying this technology to various materials are still needed for researching its applicability, especially with regard to polymer blends and composites. The purpose of this paper is to study the deposition-induced effect and the effect of compatibilizers on the mechanical properties of polypropylene and polycarbonate (PP/PC) composites. Design/methodology/approach Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Apart from studies dealing with PP as a base compound for highly filled systems, in which the polymeric part is burnt away before the sintering step, only a handful of studies on neat PP have so far been conducted for the use in ME‐AM. Next, to PP‐based blends used for ME‐AM and PP blends based on polymeric waste, Volpato et al . used neat PP for one of the first times in an extrusion‐based AM approach by feeding the material in the shape of pellets into their self‐designed piston‐driven 3D printer.…”
Section: Processing Of Neat Pp By Me‐ammentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from studies dealing with PP as a base compound for highly filled systems, in which the polymeric part is burnt away before the sintering step, only a handful of studies on neat PP have so far been conducted for the use in ME‐AM. Next, to PP‐based blends used for ME‐AM and PP blends based on polymeric waste, Volpato et al . used neat PP for one of the first times in an extrusion‐based AM approach by feeding the material in the shape of pellets into their self‐designed piston‐driven 3D printer.…”
Section: Processing Of Neat Pp By Me‐ammentioning
confidence: 99%
“…This can be a challenging factor for composites that contain high percentages of fillers. The addition of small amounts of amorphous polymers such as poly(vinyl chloride), polycarbonate (PC), or amorphous polyolefins to PP‐based composites can provide a remedy as it increases the yield strain.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, 3D-printed parts fabricated by different techniques differ in terms of strength, stiffness, microstructure and material properties, so that it is necessary to investigate their behaviors through both experimental tests and finite element analysis (FEA) [6][7][8][9][10]. Fused deposition modeling 3D printing has shown promising capabilities to improve the specific mechanical properties of parts-such as fracture toughness-by optimization of extrusion deposition trajectories [11].…”
Section: Introductionmentioning
confidence: 99%
“…Fused deposition modeling 3D printing has shown promising capabilities to improve the specific mechanical properties of parts-such as fracture toughness-by optimization of extrusion deposition trajectories [11]. It is reported that the filament direction optimization contributed to a large deformation zone leading to "ductile-like behavior", which subsequently caused a slow crack propagation rate [9]. Also, using 3D printing for developing co-continuous composite or interpenetrating phase composite parts proved a significant increase of damage tolerance and fracture toughness compared to conventionally manufacture composite parts [12].…”
Section: Introductionmentioning
confidence: 99%
“…c'). It is similar to the formation of higher interconnectivity of fiber‐type filler in the matrix that results from the introduction of cellular inclusions . Furthermore, the nanoparticles easily aggregate due to their high surface energy, and the gas separating from the melt decreases the surface energy, leading to an increased dispersal effect.…”
Section: Resultsmentioning
confidence: 99%